High levels of genetically intact HIV in HLA-DR+ memory T cells indicates their value for reservoir studies. (1st April 2020) - Horsburgh, Bethany A.; Lee, Eunok; Hiener, Bonnie; Eden, John-Sebastian; Schlub, Timothy E.; von Stockenstrom, Susanne; Odevall, Lina; Milush, Jeffrey M.; Liegler, Teri; Sinclair, Elizabeth; Hoh, Rebecca; Boritz, Eli A.; et al.
Abstract : Objective: The contribution of HLA-DR+ memory CD4 + T cells to the HIV reservoir during prolonged antiretroviral therapy is unclear as these cells are commonly excluded when assessing for replication-competent HIV. To address this issue, we examined the distribution of genetically intact HIV DNA within HLA-DR− and HLA-DR+ memory CD4 + T cells and the RNA transcriptional profile of these cells during antiretroviral therapy. Design/methods: Full-length DNA sequencing was used to examine the HIV DNA landscape within HLA-DR+ and HLA-DR− memory CD4 + T cells. RNA quantification and sequencing was used to interrogate the relationship between HLA-DR status and HIV RNA transcription. Results: HLA-DR+ CD4 + T cells contained a high frequency of genetically intact HIV genomes, contributing over half of the genetically intact viral sequences to the reservoir. Expansions of genetically identical sequences were identified in all T-cell subsets, indicating that cellular proliferation maintains genetically intact and defective viral DNA during therapy. Intracellular HIV RNA levels in HLA-DR+ and HLA-DR− T cells were not statistically different by either long terminal repeat quantitative PCR quantification or single-genome RNA sequencing of the p6-RT region. Conclusion: The high proportion of intact viral DNA sequences in the proliferative HLA-DR+ subset suggests they are critical in maintaining HIV infection during effective therapy. As such, these cells should be included in any immune intervention targeting HIV during effective therapy. Abstract : Supplemental Digital Content is available in the text